Comparison of Short-Term Outcomes Between Endovenous 1,940-nm Laser Ablation and Radiofrequency Ablation for Incompetent Saphenous Veins - Park, Insoo; Park, Sun-Cheol (Frontiers in Surgery, 2020)
Background: Radiofrequency ablation (RFA) has shown faster recovery and lower pain scores compared to Endovenous laser ablation (EVLA) for treatment of varicose veins. However, a comparison of 1,940-nm EVLA and RFA has not been reported. This study compared short-term outcomes using 1,940-nm EVLA and RFA for varicose veins. Methods: Between April 2018 and June 2018, 43 patients (83 incompetent saphenous veins) were treated with 1,940-nm EVLA and 37 patients (64 incompetent saphenous veins) with RFA. Follow-up duplex was checked at 1 month and 3 months. Results: Baseline characteristics showed no significant differences between both groups except for age. Pain scores at 6 h, and at 1, 10, and 30 days after treatment showed no differences. Complications and time to return to normal activity showed no differences. The 100% closure rate was checked in both groups at 1 month and 3 months follow-up. Conclusion: Short-term outcomes showed no significant differences between 1,940-nm EVLA and RFA treatment.